The path forward in Alzheimer's disease therapeutics: Reevaluating the amyloid cascade hypothesis. Issue 11 (3rd January 2020) - Tolar, Martin; Abushakra, Susan; Sabbagh, Marwan
Abstract: Development of disease‐modifying treatments for Alzheimer's disease (AD) has been challenging, with no drugs approved to date. The failures of several amyloid‐targeted programs have led many to dismiss the amyloid beta (Aβ) hypothesis of AD. An antiamyloid antibody aducanumab recently showed modest but significant efficacy in a phase 3 trial, providing important validation of amyloid as a therapeutic target. However, the inconsistent results observed with aducanumab may be explained by the limited brain penetration and lack of selectivity for the soluble Aβ oligomers, which are implicated as upstream drivers of neurodegeneration by multiple studies. Development of agents that can effectively inhibit Aβ oligomer formation or block their toxicity is therefore warranted. An ideal drug would cross the blood‐brain barrier efficiently and achieve sustained brain levels that can continuously prevent oligomer formation or inhibit their toxicity. A late‐stage candidate with these attributes is ALZ‐801, an oral drug with a favorable safety profile and high brain penetration that can robustly inhibit Aβ oligomer formation. An upcoming phase 3 trial with ALZ‐801 in APOE4/4 homozygous patients with early AD will effectively test this amyloid oligomer hypothesis.